2004
DOI: 10.1300/j051v13n01_01
|View full text |Cite
|
Sign up to set email alerts
|

Self-Advocacy Skills in Asian American Parents of Children with Developmental Disabilities

Abstract: The level of self-advocacy skills in Asian American parents of young children with developmental disabilities was assessed. The relationship of self-advocacy skills with social support and with disability-based discrimination was investigated. Correlates of self-advocacy skills were explored. Asian American parents of young children with developmental disabilities in this study scored a significantly lower level of assertiveness and other self-advocacy skills than did their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…2004). Studies have also found that Asian mothers tend to have fewer self‐advocacy and assertiveness skills than their non‐Asian counterparts (Huang et al. 2004); thus, Chinese mothers may have a greater need to boost up their relationship efficacy in dealing with their child, other family members and the larger social circles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2004). Studies have also found that Asian mothers tend to have fewer self‐advocacy and assertiveness skills than their non‐Asian counterparts (Huang et al. 2004); thus, Chinese mothers may have a greater need to boost up their relationship efficacy in dealing with their child, other family members and the larger social circles.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, parent intervention programmes have incorporated aspects of relationship coping and have shown effectiveness in enchancing support, improving self-efficacy and reducing stress (Hudson et al 2003;Sanders et al 2004). Studies have also found that Asian mothers tend to have fewer selfadvocacy and assertiveness skills than their non-Asian counterparts (Huang et al 2004); thus, Chinese mothers may have a greater need to boost up their relationship efficacy in dealing with their child, other family members and the larger social circles. With a combination of mutual support and skill-based training in assertiveness and self-advocacy, not only can their problem-focused coping strategies be strengthened, but parents' relationship-focused coping can also be enhanced with the aim of further increasing their positive perceptions.…”
Section: Implications Of the Studymentioning
confidence: 99%
“…15,16 Participants explained that developmental disabilities may result from mistakes by themselves or their ancestors, omissions (such as improper burial location), or a "spiritual curse." As a result of these beliefs, community members often feel that accepting services or support from others is inappropriate.…”
Section: Cultural Factorsmentioning
confidence: 99%
“…Active versus passive participation varies relative to the family and level of acculturation (Rodriguez & Olswang, 2003). For example, some studies have indicated that Asian American parents of children with disabilities were reported to be less assertive, and they exhibited fewer selfadvocacy skills than did non-Asian American parents (Huang et al, 2004). By contrast, Parette, Chuang, and Huer (2004) found first-generation Chinese families differed from other Asian American families in that they were involved advocates for their child.…”
Section: Structuring Relationships (S)mentioning
confidence: 99%